Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3390/admsci2010063
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and Knowledge Management in an E-Government Environment

Abstract: Abstract:The Malcolm Baldrige National Quality Award (MBNQA) is well known to assess quality and business processes in a variety of sectors, including government. In this study, we investigate the relationship between aspects of the MBNQA's leadership triad and knowledge management in an e-government context. Specifically, we survey 1,100 employees of a medium-sized city government in the United States to investigate the relationship between leadership triad components, leadership strategic planning, and custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
0
7
0
9
Order By: Relevance
“…Extending the previously mentioned issues influencing the knowledge sharing capabilities in e-government context, employees need more support and a well-structured plan for learning and awareness. In a study that used responses from 1,100 public employees in the USA, the researchers concluded that leadership efforts are needed to support employee's learning and innovation and ensure that the organizational functional capabilities are well evaluated continuously (Ryan et al, 2012). The authors also concluded that ICT is important for leadership to facilitate KM processes in an e-government context.…”
Section: Tg 123/4mentioning
confidence: 99%
“…Extending the previously mentioned issues influencing the knowledge sharing capabilities in e-government context, employees need more support and a well-structured plan for learning and awareness. In a study that used responses from 1,100 public employees in the USA, the researchers concluded that leadership efforts are needed to support employee's learning and innovation and ensure that the organizational functional capabilities are well evaluated continuously (Ryan et al, 2012). The authors also concluded that ICT is important for leadership to facilitate KM processes in an e-government context.…”
Section: Tg 123/4mentioning
confidence: 99%
“…Strategic management research, using a knowledge-based view of the firm, mentions both strategic flexibility (Chen et al 2017;Guo and Cao 2014) and an organization's ability to manage its knowledge internally (Scuotto et al 2017;Del Giudice and Peruta 2016;Ryan et al 2012) as essential for supporting strategic renewal goals (Hughes and Mustafa 2017;Del Giudice et al 2013a, 2013b. These factors are assumed to link synergistically (Chen et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts to define tacit knowledge later acknowledged that it can be compared to objective knowledge, and that become one of the conversional definitions of tacit knowledge and established by many authorities in knowledge management literature [11]. In some explanations Smith [12], opined that it is the type of knowledge shared using symbolic gestures or signs between individuals and groups.…”
Section: Literature Review 21 Objective Knowledgementioning
confidence: 99%